East-West Dichotomy: gaps, interaction, intercrossing - Zheleznyak, Olga (project baikal, 2017)
The article studies the forms of interaction, gaps and intercrossing between the paradigms of East and West. Interpretation of the dichotomy as a model and value of culture and as a significant component of the worldview is presented in the article as a process of combination of cultural norms within the Whole. The idea of ‘transmutation contact’ is proposed for the discussion of peculiarities of the notion East-West. The mobility of borders and the ambiguity of the notion East-West predetermine different discourses of the discussion in the spaces of rational-irrational, tradition-nontradition, enlightenment and barbarism. It can be explained by the fact that the East-West dichotomy is integrated in the universe, the microspace and macrospace.